Forecasting The Share Price of PT Merdeka Copper Gold Tbk By Using Arch-Garch Model - Nabilah Faisal, Ananda; Nababan, ESM; Sutarman, Sutarman; Gultom, Parapat (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to obtain a forecasting model and compare PT Merdeka Copper Gold Tbk share price using the time series method, ARCH-GARCH model. The data used is historical data for the period December 2021 – December 2022. The initial steps are the stationarity test, identifying the ARIMA model, and checking the heteroscedasticity effect of the best ARIMA model. Then from this model, identify the ARCH-GARCH model. After the model has been formed, compare those models that have been assumed by using the smallest AIC and SBC values and checking the model's heteroscedasticity effect. The last step is forecasting for January 2023 using GARCH (1,0). The equation is .